Uncovering the drivers, impacts, and urgent solutions to soil erosion in the Ethiopian Highlands: a global perspective on local challenges - Teku, Degfie; Derbib, Tarekegn (Frontiers in Environmental Science, 2025)
Soil erosion in the Ethiopian Highlands is a critical environmental challenge, driven by both natural and anthropogenic factors such as deforestation, overgrazing, unsustainable agricultural practices, and climatic variability. Addressing this issue is essential for safeguarding the region’s agricultural productivity, biodiversity, and socio-economic stability. This review aims to synthesize and evaluate existing research on the extent, impacts, and mitigation strategies of soil erosion across the Ethiopian Highlands, with a focus on informing sustainable land management practices and policy interventions. The review draws on findings from 129 peer-reviewed studies and reports, providing a comprehensive national-scale assessment of soil erosion. The selected literature encompasses empirical field studies, remote sensing analyses, and policy evaluations. The reviewed literature highlights severe soil degradation, with erosion rates in some areas exceeding 200 tonnes per hectare annually, resulting in the loss of over 1.5 billion tonnes of topsoil each year. This degradation reduces agricultural productivity by 5%–10% annually and causes economic losses exceeding $1 billion, approximately 2% of Ethiopia’s GDP. The impacts of soil erosion extend to water quality, biodiversity, and rural livelihoods. Mitigation strategies such as terracing, stone bunds, and agroforestry have demonstrated potential to reduce soil loss by up to 60%, stabilize slopes, and enhance soil organic matter. This review underscores the urgency of integrated and scalable approaches to combat soil erosion, combining sustainable land management practices, supportive policy frameworks, and active community engagement.